Influence of Binders and Solvents on Stability of Ru/RuOx Nanoparticles on ITO Nanocrystals as Li–O2 Battery Cathodes. Issue 3 (23rd January 2017) - Vankova, Svetoslava; Francia, Carlotta; Amici, Julia; Zeng, Juqin; Bodoardo, Silvia; Penazzi, Nerino; Collins, Gillian; Geaney, Hugh; O'Dwyer, Colm
Abstract: Fundamental research on Li–O2 batteries remains critical, and the nature of the reactions and stability are paramount for realising the promise of the Li–O2 system. We report that indium tin oxide (ITO) nanocrystals with supported 1–2 nm oxygen evolution reaction (OER) catalyst Ru/RuO x nanoparticles (NPs) demonstrate efficient OER processes, reduce the recharge overpotential of the cell significantly and maintain catalytic activity to promote a consistent cycling discharge potential in Li–O2 cells even when the ITO support nanocrystals deteriorate from the very first cycle. The Ru/RuO x nanoparticles lower the charge overpotential compared with those for ITO and carbon‐only cathodes and have the greatest effect in DMSO electrolytes with a solution‐processable F‐free carboxymethyl cellulose (CMC) binder (<3.5 V) instead of polyvinylidene fluoride (PVDF). The Ru/RuO x /ITO nanocrystalline materials in DMSO provide efficient Li2 O2 decomposition from within the cathode during cycling. We demonstrate that the ITO is actually unstable from the first cycle and is modified by chemical etching, but the Ru/RuO x NPs remain effective OER catalysts for Li2 O2 during cycling. The CMC binders avoid PVDF‐based side‐reactions and improve the cyclability. The deterioration of the ITO nanocrystals is mitigated significantly in cathodes with a CMC binder, and the cells show good cycle life. In mixed DMSO–EMITFSI [EMITFSI=1‐ethyl‐3‐methylimidazolium bis(trifluoromethylsulfonyl)imide] ionic liquid electrolytes, the Ru/RuO x /ITO materials in Li–O2 cells cycle very well and maintain a consistently very low charge overpotential of 0.5–0.8 V. Abstract : Building better batteries : Indium tin oxide (ITO) nanocrystals with supported 1–2 nm Ru/RuO x nanoparticles (NPs) demonstrate efficient oxygen evolution reaction (OER) processes for Li–O2 battery cathodes. The Ru/RuO x NPs are most effective in DMSO electrolytes with a carboxymethyl cellulose (CMC) binder. ITO is found to be unstable from the first cycle and the Ru/RuO x NPs remain effective OER catalysts for efficient Li2 O2 during cycling.